Isu Global Konvergensi IFRS: Masalah Pengukuran Menggunakan Fair Value Accounting - Sonoto, John F. (Widya Mandala Surabaya Catholic University, 2010)
This paper aims to describe one of the global issues of IFRS convergence in Indonesia which is the measurement by using the fair value in relation to the information generated based on the qualitative characteristics of information. Globalized development itself requires good accounting standards required by the capital markets or institutions that have an agency problem caused by the problem of distance between the Principle and agent. The phenomenon is then pushed the International Accounting Standards Boards convergence of international accounting standards with IFRS. Financial statements based on historical cost fail to provide early warning signals about the financial difficulties being experienced by financial institutions. Issue is then a very strong incentive to apply the fair value method instead of historical cost.